2022
DOI: 10.1523/eneuro.0337-21.2022
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Electrographic Signatures Generated by Mechanistically-Diverse Seizurogenic Compounds in the Larval Zebrafish Brain

Abstract: We assessed similarities and differences in the electrographic signatures of local field potentials evoked by different pharmacological agents in zebrafish larvae. We then compared and contrasted these characteristics with what is known from electrophysiological studies of seizures and epilepsy in mammals, including humans. Ultimately, our aim was to phenotype neurophysiological features of drug-induced seizures in larval zebrafish for expanding knowledge on the translational potential of this valuable alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Pinion induced seizures in 4dpf zebra sh using different pro-convulsants and recorded their EEG. The local eld potentials (LFP) of the larval zebra sh were similar to the characteristics exhibited by the mammalian central nervous system 7 . In addition, pro-convulsant agents can cause behavioral disorders of zebra sh, such as unstable swimming, hyperactivity, loss of posture, and the overexcitation of neurons 10 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Pinion induced seizures in 4dpf zebra sh using different pro-convulsants and recorded their EEG. The local eld potentials (LFP) of the larval zebra sh were similar to the characteristics exhibited by the mammalian central nervous system 7 . In addition, pro-convulsant agents can cause behavioral disorders of zebra sh, such as unstable swimming, hyperactivity, loss of posture, and the overexcitation of neurons 10 .…”
Section: Discussionmentioning
confidence: 81%
“…Danio rerio, is an emerging model animal with a small size, easy reproduction, transparent embryos, and a short growth cycle 4 , and it is easier to raise than standard experimental animals. The following features make zebra sh a useful model in the study of seizures as well as to conduct highthroughput drug screening 5,6 , such as access to local eld potential (LFP) recordings 7 , in vivo brain imaging via activity-dependent bioluminescent/ uorescent reporters 8 , the ever-expanding genetic toolbox 9 . A past research reported that larval zebra sh treated with pro-convulsant agents develop seizure-like behavior in three main stages 10 : stage I is characterized by increased swimming speed, stage II by fast swirly swimming, and stage III by the loss of body balance and rollover.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the monitoring of the local field potential in ZF brains has been widely performed to investigate the possible electrographic effects or changes in ZF treated with different drugs and convulsants [31,63,82,88,119]. Even if these kinds of measurements are extensively employed in ZF, the precise electrographic characteristics of electrographic seizures in these organisms after treatment with different compounds/drugs are little known [120]. These electrographic measurements are often applied to larvae.…”
Section: Electrophysiological Techniquesmentioning
confidence: 99%
“…Zebrafish larvae between 3 and 7 dpf are usually embedded in 1.2-2% low-melting-point agarose prepared in an embryo medium. One or two glass microelectrodes filled with NaCl (2 M) or with artificial cerebrospinal fluid (124 mM NaCl, 10 mM glucose, 2 mM KCl, 2 mM MgSO 4 , 2 mM CaCl 2 , 1.25 mM KH 2 PO 4 , and 26 mM NaHCO 3 NaCl) are inserted through the epidermis, into the intracranial space, into the midbrain or optic tectum or forebrain [31,63,77,78,82,87,88,91,92,[119][120][121][122][123][124]. Then, the larvae are usually treated with different doses of chemicals/drugs, and the activity is measured for 10-30 min and the obtained seizure events are compared to one of the control samples (untreated larvae).…”
Section: Electrophysiological Techniquesmentioning
confidence: 99%
See 1 more Smart Citation